Postural Orthostatic Tachycardia Syndrome (POTS) – A Review of Pathophysiological Mechanisms, Diagnosis and Therapy - Dziedzic, Alicja; Furtak, Daria; Grela, Wiktor; Niewiadomska, Jagoda; Głogowska, Paulina; Tulej, Dawid; Marciniuk, Dominika; Gniaź, Natalia; Górska, Aleksandra; Marko, Natalia (Journal of Education, Health and Sport, 2024)
Introduction Postural Orthostatic Tachycardia Syndrome (POTS) is a chronic disorder of the autonomic nervous system. It is characterized by orthostatic tachycardia and orthostatic intolerance upon standing, without low blood pressure. It affects multiple body systems, leading to a wide range of symptoms that contribute to debilitation and reduced functionality. The disorder has significant functional and economic consequences, although its underlying mechanisms remain only partially understood. Many POTS patients receive inadequate care due to limited understanding of the etiology of POTS, a lack of evidence-based treatment options, and minimal training among physicians in recognizing and managing POTS. Aim of the study The purpose of this review is to provide a comprehensive overview of POTS, including its etiology, associated comorbidities, diagnostic challenges, and approaches to diagnosis, as well as potential pharmacological and non-pharmacological treatment options. Material and Method The literature search methodology involved using the keyword "POTS" in combination with terms such as "etiology," "treatment," "diagnosis," "symptoms," "long COVID-19," and "exercise." Searches were conducted in the PubMed and Google Scholar databases, focusing primarily on review articles and clinical trials. Conclusions Raising awareness of POTS among physicians is essential for delivering optimal healthcare to patients. Despite the prevalence of POTS and its significant impact on patients' lives, research funding remains disproportionately low. Strengthening research infrastructure is crucial to understand the pathophysiology of POTS and to standardize evaluation tools, outcome measures, and patient care.